Harm reduction, evidence-based practices and prevention of drug use - Silva Ricetti , Eduardo; Eduarda Orlando , Maria; Alecsander Reichert , Richard; de Oliveira Lavezzo , Beatriz; Gabrieli Reichert , Karoline (Seven Editora, 2023)
This paper aims to present a literature review of the last five years that examines the characteristics of programs, policies, and actions in Brazil.  The article addresses the concept of evidence-based preventive practices, establishing relationships between the prevention of drug use in Brazilian school contexts and Harm Reduction, based on the assumption that evidence-based preventive practices are essential to ensure the right of access to comprehensive approaches to people who use drugs.   Thus, it is expected to contribute to the formulation and implementation of effective, effective and bioethical interventions in the field of prevention of alcohol and other drug use.DOI: https://doi.org/10.56238/devopinterscie-098